Implementasi Program Pendaftaran Tanah Sistematis Lengkap (PTSL) di Kabupaten Kebumen - Cahyono, Joko Pitoyo (Public Policy and Management Inquiry, 2022)
The implementation of land policies are still experiencing many obstacles, so that there are still many land conflicts that occur in the community. This study aims to determine and analyze aspects of communication, resources, disposition and bureaucratic structure in determining the achievement of the implementation of the Complete Systematic Land Registration Program (PTSL) in Kebumen Regency.The method used in this research is qualitative method. The research was conducted in Kebumen Regency. Data was collected through interviews, observation and documentation. Data analysis was carried out by using interactive model analysis method and testing the validity of the data by using triangulation technique. The results of the study illustrate that the communication aspect has been running effectively, such as the publication mechanism, the coordination system and information disclosure have been fulfilled properly. The aspect of resources is a factor that hinders the achievement, firstly, the lack of implementing human resources as a driving team that must reach all sub-districts, secondly, self-supporting financing that is self-subsistent which was mutually agreed was deemed too much for some people, while the subsidy provided by the Kebumen Regency government was not sufficient. Aspects of disposition and bureaucratic structure are factors that support the successful implementation, in areas with high achievement caused that they can mobilize activities independently, while in areas with low achievement due to the lack of commitment and involvement of the district government in realizing the budget allocation. The formation of an adjudication committee that has not met the structure and the low support from the village government to mobilize community participation. in the aspect of the bureaucratic structure, the establishment of the PTSL implementing committee at the village level did not run as it should. Keywords: Bureaucratic Structure, Communication, Disposition, Implementation, Land Policy, Resources